2013
DOI: 10.1590/s0102-67202013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica sócio-familiar com pacientes portadores de ostomia intestinal definitiva

Abstract: -Rational:The person who undergoes a definitive intestinal ostomy experience significant changes in social and family dynamics. Most of the time the patients are fragile by risk due to the new situation. Aim: To analyze the social dynamics of people with permanent intestinal stoma. Method: Qualitative research on the basis of information collected at the time of the monthly withdrawal of collecting handbags and accessories provided by the unified Health System. Were part of the study 12 users of São Miguel do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 2 publications
0
14
0
16
Order By: Relevance
“…This finding is unexpected as married individuals are normally considered to have greater support and acceptance. On the other hand, this finding may be explained by the fact that a chronic disease that causes increasing dependence can be a source of conflict and strengthen or weaken affective ties and family bonds 14,27 . While in the present study older age among individuals in the moderate stage was related to worse scores for ADLs and cognition in the PDQ-39, in a study by Tedrus et al, 28 the greatest impairment was observed for the ADL and mobility domains.…”
mentioning
confidence: 99%
“…This finding is unexpected as married individuals are normally considered to have greater support and acceptance. On the other hand, this finding may be explained by the fact that a chronic disease that causes increasing dependence can be a source of conflict and strengthen or weaken affective ties and family bonds 14,27 . While in the present study older age among individuals in the moderate stage was related to worse scores for ADLs and cognition in the PDQ-39, in a study by Tedrus et al, 28 the greatest impairment was observed for the ADL and mobility domains.…”
mentioning
confidence: 99%
“…Usually the questioning and anger are a necessary step, given the impact of the stoma on their lives, which culminates in acceptance and mental adaptation to changes after a period of recovery and learning about the physical changes. 14 Within this category, there was a significant portion of people undergoing ostomy surgery who had never seen a stoma nor did they know that this surgical procedure existed. Therefore, the strangeness of the stoma image and dynamics of elimination in their bodies could have repercussions on peoples' lives, now with a stoma, and they started to feel different from the rest of society.…”
Section: Discussionmentioning
confidence: 99%
“…22 In the process of adaptation, there may be moments of progress and setbacks, resulting in an evolution in coping with difficult situations. The daily life routine, with return to society, can represent moments of significantly expressed difficulties which can be complex, such as shame, fear, insecurity and especially embarrassment, 14 with repercussions that may at first seem negative. However, during these moments one can establish coping strategies, strengthening the person with a stoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quando se tem que sair, quem tem a estomia, tem que se certificar se tem banheiros bons nos locais aonde vai. (E8) Para os entrevistados, lidar com esvaziamento da bolsa coletora possui particularidades, sendo recomendável que realizem antes que encha 1/3 de sua capacidade, determinando que os estomizados esvaziem a bolsa em média de cinco a dez vezes ao dia, para evitar o risco de rompimento e descolamento da mesma do abdômen (13) . Para tanto, a existência de um local com condições mínimas de higiene e estrutura física, como a presença de uma pia e um vaso sanitário localizados em um mesmo espaço, com privacidade, para realizar o esvaziamento ou a troca da bolsa, é imprescindível, pois tanto a limpeza quanto a troca da bolsa de estomia podem expor os estomizados a constrangimentos públicos pela sua condição.…”
Section: Influência Da Estomia No Convívio Socialunclassified